Map of the imperial residential city of Vienna - Unknown:::Creator::::::::::::; Meyer, Joseph, 1796-1856 (author):::Contributor:::::::::::: (Bibliographisches Institut; Hildburghausen; Germany)
Map of Vienna, including miniature engravings of 12 landmarks in Vienna: K.K. Burg, Kloster und Kirche der Salesianerinnen, K.K. Med. Chr. Josephsacademie, Lichtensteinischer Pallast, Carlskirche, Reitschule und Hoftheater, Neues Burgthor, Belvedere, Bahnhof der Wien-Raaber Eisenbahn, Universität, Maria-Stiegen Kirche, Stephanskirche.